2022
DOI: 10.3389/fmicb.2022.999876
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic and eukaryotic microbial diversity from three soda lakes in the East African Rift Valley determined by amplicon sequencing

Abstract: Soda lakes are unique poly-extreme environments with high alkalinity and salinity that support diverse microbial communities despite their extreme nature. In this study, prokaryotic and eukaryotic microbial diversity in samples of the three soda lakes, Lake Abijata, Lake Chitu and Lake Shala in the East African Rift Valley, were determined using amplicon sequencing. Culture-independent analysis showed higher diversity of prokaryotic and eukaryotic microbial communities in all three soda lakes than previously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…In this study, most of the GH genes identified were found to likely originate from bacteria belonging to the genus of Halomonas, which corresponds to Halomonas as one of the most abundant genera in our previous work on the microbial diversity of Ethiopian lakes using amplicon metagenomics ( Jeilu et al, 2022 ). Halomonas have, in previous investigations, been reported to be one of the most abundant prokaryotes in soda lakes ( Humayoun et al, 2003 ; Dimitriu et al, 2008 ; Asao et al, 2011 ; Lanzén et al, 2013 ; Sorokin et al, 2014 ), responsible for the biogeochemical cycling and the immediate degradation of organic matter produced by autotrophic bacteria like cyanobacteria ( Jones and Grant, 1999 ; Sorokin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 64%
“…In this study, most of the GH genes identified were found to likely originate from bacteria belonging to the genus of Halomonas, which corresponds to Halomonas as one of the most abundant genera in our previous work on the microbial diversity of Ethiopian lakes using amplicon metagenomics ( Jeilu et al, 2022 ). Halomonas have, in previous investigations, been reported to be one of the most abundant prokaryotes in soda lakes ( Humayoun et al, 2003 ; Dimitriu et al, 2008 ; Asao et al, 2011 ; Lanzén et al, 2013 ; Sorokin et al, 2014 ), responsible for the biogeochemical cycling and the immediate degradation of organic matter produced by autotrophic bacteria like cyanobacteria ( Jones and Grant, 1999 ; Sorokin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 64%
“…Actual participation in the degrader community may be indicated by the fitness of isolates of certain species in the extreme conditions arising in saline lakes. The use of metabarcoding to study the mycobiota of salt lakes would undoubtedly reveal a greater diversity of OTUs that can be found in samples [83,84]. Nevertheless, this does not exclude them but makes it necessary to use methods that allow for isolating these organisms in culture, assessing their adaptive capabilities, and searching for valuable secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, predation can display as positive synchronous associations when a prey attracts its predators to a habitat patch or as negative (both synchronous and time-shifted) when predators eliminate their preys 73,74 . Various positive keystone eOTUs abundant in spring were assigned to predatory flagellates such as Colpodellida 75 or intracellular parasitic taxa such as Cryptomycotina 76 and Perkinsozoa 77 which are common in aquatic habitats 78 . These, together with the significant effect of Daphnia magna on microeukaryotic community structure suggest an important role of top-down controls in spring.…”
Section: Discussionmentioning
confidence: 99%